Early enteral nutrition with fructooligosaccharides improves prognosis in severe acute pancreatitis - Fangchun Liu; Zhiming Xiao; Hongyan Zeng; Jingbo Li; Feiyan Ai; Jing Qi (Scientific Reports)
Abstract Soluble dietary fiber, notably as an adjunct to early enteral nutrition (EEN), is gaining prominence in clinical therapy. This study evaluates the effect of fructooligosaccharides (FOS), a new soluble dietary fiber, on the prognosis of patients with severe acute pancreatitis (SAP). In a retrospective cohort study at the Third Xiangya Hospital of Central South University from July 2017 to July 2023, 110 SAP patients were analyzed. TPF (enteral nutritional suspension of total protein)-normal and TPF-FOS groups both received standard EEN solutions; the latter additionally received FOS. Outcomes were compared between the groups. The study included 37 patients in the TPF-FOS group and 73 patients in the TPF-normal group. Mortality was 13.50% in the TPF-FOS group and 34.20% in the TPF-normal group (P < 0.05). FOS was identified as an independent protective factor (OR: 0.826, P = 0.041). The TPF-FOS group showed lower rates of intra-abdominal infection and decreased the level of inflammation (P < 0.05). FOS potentially acts as an independent protective factor against death in SAP. Additionally, the supplementation of EEN with FOS may contribute to reducing mortality and improving the prognosis of SAP patients.